2020
DOI: 10.1016/j.jmatprotec.2020.116809
|View full text |Cite
|
Sign up to set email alerts
|

Machinability of inconel 718 during turning: Cutting force model considering tool wear, influence on surface integrity

Abstract: Machining accuracy can be compromised by elastic workpiece deformation and subsurface residual stress introduction during cutting. In order to anticipate the impact of cutting forces and surface integrity evolutions on finished surface and its geometrical errors, it is necessary to better understand the influence of cutting conditions and tool wear. In this study, machinability of Inconel 718 using a round carbide tool in finish turning conditions is assessed. Cutting forces evolution during tool life are anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…The experiment involves machining tests on 6 discs with different conditions summed up in Table 1. The cutting conditions are consistent with semi finishing and finishing conditions identified in [17]. The tests consist in 3 consecutive face turning passes.…”
Section: Experimental Conditionsmentioning
confidence: 60%
See 3 more Smart Citations
“…The experiment involves machining tests on 6 discs with different conditions summed up in Table 1. The cutting conditions are consistent with semi finishing and finishing conditions identified in [17]. The tests consist in 3 consecutive face turning passes.…”
Section: Experimental Conditionsmentioning
confidence: 60%
“…As mentioned in the introduction section, machining with a worn tool may create high tensile stresses close to the machined surface. However, the affected depth and magnitude of the compressive peak are also significantly increased compared to machining with a fresh tool [14,17]. Based on these bibliographic knowledge and experimental observations, it is deduced that the residual stress profiles obtained with a worn tool are highly compressive in the studied case.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…It was found that the Bayesian inference can predict cutting and ploughing forces with minimal initial data, which means that this method is a preferred approach when the initial data are very reduced and there is inherent uncertainty. In the recent study presented by Toubhans et al [48], a cutting force model for the turning of Inconel 718 was developed, which enables the prediction of cutting forces and their evolution along the tool pass, for a wide range of surface finish levels of quality. The authors found that including a component relative to the chip flow direction in the local force model allows for better force predictions.…”
Section: Cutting Force Prediction Methodsmentioning
confidence: 99%